An Experiential Learning in Web Technology Course - Bhajantri, Vijayakumar; Sujatha, C.; Yaligar, Shilpa; Pawar, Manjula K. (Journal of Engineering Education Transformations, 2016)
Web Technology is the development of the mechanism that allows two of more computer devices to communicate over a network. To understand such a complex system there is a need of experiential learning. Authors adopted an "Experiential learning" for teaching the web technology course. Teaching with a hands-on session where the teacher explains the concepts with demonstration and students simultaneously practice& also modify the fields to observe the change. After the end of chapter the students learning is verified by giving the structured enquiry category assignments and are evaluated. At the end of delivery of course I,e one month before the term end the collective learning is verified through the course project. Two course projects are carried out by the students as a team of two. One is the intranet project, where student understands how to connect and work in a local area network and the other is internet project, where student learns how to host a website globally. In both the projects students worked on LINUX platform with LAMP as a framework and developed web apps using HTML5, CSS 3, Jquery, PHP and SQL. The experiential learning enhanced the student's domain knowledge of Linux architecture, computer networks, and web and database servers applying in real time scenarios. Finally we conclude such practical/programming oriented courses should be designed as hands-on lab courses.